THE EFFECT OF DIGITAL MEDIA ON THE DEVELOPMENT OF EARLY CHILDHOOD READING SKILLS - Sihotang, Elina Rosa; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
The extensive incorporation of digital media in children's lives has greatly affected their reading patterns and literacy growth. This research examines how digital media impacts the evolution of reading abilities in early childhood. It looks into the benefits and obstacles that digital tools present in promoting literacy. Using a mixed-methods strategy, information was collected via surveys, interviews, and observations involving children aged 6-12, along with their parents and educators. Results indicate that although digital media provides engaging and interactive literacy experiences, too much dependence may weaken conventional reading habits. The study highlights the importance of a balanced method for incorporating digital media and nurturing a robust reading environment.